1995
DOI: 10.1042/cs0890083
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Induces Upregulation of Neutral Endopeptidase 24.11 on Human Neutrophils: Involvement of the CD14 Receptor

Abstract: 1. As lipopolysaccharide is a major stimulator of neutrophil responses during Gram-negative bacterial infections, we studied its effect on the membrane expression of neutral endopeptidase 24.11/CD10 on neutrophils in a model of endotoxaemia in vitro. Lipopolysaccharide added to human whole-blood induced a marked and sustained CD10/neutral endopeptidase upregulation that was already detectable at 0.1 ng/ml and was maximal at a lipopolysaccharide concentration of 10 ng/ml. 2. We observed that neither tumour necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Our data confirm results from Koch, who as early as 1991 described CD13 as a monocytic activation‐related antigen, which is up‐regulated by LPS [7]. Neprilysin/CD10 expression on neutrophils has also been described as increasing within 1 h after LPS exposure [29]. IL‐10 treatment of PBMC resulted in a down‐regulation of both HLA‐DR and CD13 expression on monocytes.…”
Section: Discussionsupporting
confidence: 88%
“…Our data confirm results from Koch, who as early as 1991 described CD13 as a monocytic activation‐related antigen, which is up‐regulated by LPS [7]. Neprilysin/CD10 expression on neutrophils has also been described as increasing within 1 h after LPS exposure [29]. IL‐10 treatment of PBMC resulted in a down‐regulation of both HLA‐DR and CD13 expression on monocytes.…”
Section: Discussionsupporting
confidence: 88%
“…CD10 expression on the neutrophil surface seems to be up-regulated by many factors, such as lipopolysaccharide and granulocyte/macrophage-colony-stimulating factor (Connelly et al 1993;Fagny et al 1995). A close association of CD10 expression with some diseases has been described.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, only 1 study has reported that CD10 expression may slightly increase in neutrophils incubated with lipopolysaccharide (LPS), but this was observed to occur in vitro. 45 Similarly, CD10 enzymatic activities have been shown to either decrease or increase upon in vitro stimulation of neutrophils with, respectively, phorbol 12-myristate 13-acetate, 46 or formyl-methionyl-leucyl phenylalanine, C5a, LPS, or granulocyte-macrophage colony-stimulating factor. 47 23 The latter cells, however, displayed their immunosuppressive properties via CD11b-mediated cell contacts and reactive oxygen species production but not ARG1 release.…”
mentioning
confidence: 99%